Hemodynamic Response of the Supplementary Motor Area during Locomotor Tasks with Upright versus Horizontal Postures in Humans - Arito Yozu; Shigeru Obayashi; Katsumi Nakajima; Yukihiro Hara (Neural Plasticity)
To understand cortical mechanisms related to truncal posture control during human locomotion, we investigated hemodynamic responses in the supplementary motor area (SMA) with quadrupedal and bipedal gaits using functional near-infrared spectroscopy in 10 healthy adults. The subjects performed three locomotor tasks where the degree of postural instability varied biomechanically, namely, hand-knee quadrupedal crawling (HKQuad task), upright quadrupedalism using bilateral Lofstrand crutches (UpQuad task), and typical upright bipedalism (UpBi task), on a treadmill. We measured the concentration of oxygenated hemoglobin (oxy-Hb) during the tasks. The oxy-Hb significantly decreased in the SMA during the HKQuad task, whereas it increased during the UpQuad task. No significant responses were observed during the UpBi task. Based on the degree of oxy-Hb responses, we ranked these locomotor tasks as UpQuad > UpBi > HKQuad. The order of the different tasks did not correspond with postural instability of the tasks. However, qualitative inspection of oxy-Hb time courses showed that oxy-Hb waveform patterns differed between upright posture tasks (peak-plateau-trough pattern for the UpQuad and UpBi tasks) and horizontal posture task (downhill pattern for the HKQuad task). Thus, the SMA may contribute to the control of truncal posture accompanying locomotor movements in humans.